2004
DOI: 10.1029/2003gl019232
|View full text |Cite
|
Sign up to set email alerts
|

Strong seismic reflections and melts in the mantle of a continental back‐arc basin

Abstract: A program of explosion seismology in central North Island, New Zealand, discovered a strong reflector within the upper mantle. Reflections from this (PmP2) are spatially confined to come from an interface 35 km deep and directly beneath a 40 km‐wide, back‐arc extension zone with active volcanism, high heat flow, low Pn wave‐speeds and thinned crust. On the basis of relative reflection amplitudes, the mantle reflections are most readily explained by an interface with a negative seismic impedance contrast. A sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 26 publications
6
93
1
Order By: Relevance
“…An increase in velocity beneath this region might cause a similar reflection; Harrison and White (2004) deduced that a 16 km-thick quartzo-feldspathic crust is underlain to ~30 km depth beneath the Central North Island by a mafic material containing at least 2% partial melt. In contrast, Stratford and Stern (2004) reported an increase in seismic velocity for the same depth interval beneath the region and suggested that the velocity structure from 16 to 30 km depth represents the presence of anomalously low-velocity upper mantle. Another possible factor is that of reflection due to lateral variations in crustal structure (i.e.…”
Section: Results and Discussion A Attenuation Functionmentioning
confidence: 83%
“…An increase in velocity beneath this region might cause a similar reflection; Harrison and White (2004) deduced that a 16 km-thick quartzo-feldspathic crust is underlain to ~30 km depth beneath the Central North Island by a mafic material containing at least 2% partial melt. In contrast, Stratford and Stern (2004) reported an increase in seismic velocity for the same depth interval beneath the region and suggested that the velocity structure from 16 to 30 km depth represents the presence of anomalously low-velocity upper mantle. Another possible factor is that of reflection due to lateral variations in crustal structure (i.e.…”
Section: Results and Discussion A Attenuation Functionmentioning
confidence: 83%
“…Reyners et al 2006;Sherburn et al 2003Sherburn et al , 2006, explosion seismology (e.g. Harrison & White 2004;Stratford & Stern 2004 and magnetotelluric studies (Ogawa et al 1999).…”
Section: Subsurface Structure Of Tvzmentioning
confidence: 98%
“…2) within the mantle wedge (Stratford & Stern 2004), but Harrison & White (2004) believe this simply represents the base of the under-plated basaltic crust. This may reflect a pool of magma within the mantle wedge.…”
Section: Subsurface Structure Of Tvzmentioning
confidence: 99%
See 1 more Smart Citation
“…associated with the volcanism are crustal thinning (Harrison & white 2004;Stratford & Stern 2004) and active extension (wallace et al 2004) with a measured extension rate in the vicinity of lake Taupo of 9 ± 3 mm/yr, the motion being normal to the trend of the TVZ (darby et al 2000). South of the Mangakino caldera the zone of rifting and crustal thinning lies between bounding fault zones (kaingaroa Fault and Hauhungaroa Fault, Fig.…”
Section: Introductionmentioning
confidence: 99%